Invasive infection due to Saprochaete capitata in a young patient with hematological malignancies - Parahym, Ana Maria Rabelo de Carvalho (Braz J Microbiol, 2015)
We report a case of invasive infection due to Saprochaete capitata in a patient with hematological malignancies after chemotherapy treatment and empiric antifungal therapy with caspofungin. Although severely immunocompromised the patient survived been treated with amphotericin B lipid complex associated with voriconazole.